Faktor-Faktor yang Berkontribusi dalam Pengembangan Strategi Pembelajaran Pendidikan Islam - Torik, Muh. Fauzan (Tsamratul Fikri | Jurnal Studi Islam, 2021)
Education is an activity that every human being must engage in in order to minimize the sense of ignorance that exists in every human being and to provide a means of living in the world. With knowledge, we can learn a variety of things that will lead us to a time when we know more. The education process is not just to do the process of seeking knowledge, but the need for something that supports the development of educational learning itself, one of which is something that contributes to the development of learning, especially in Islamic education learning. This intends to look for any factors that support the development strategy of educational learning. Sometimes educators, teachers, or lecturers assume that the factors that inhibit learning come from learners, even though it is not entirely blamed on learners, but many factors that really contribute to helping learners in the implementation of learning can develop, both in terms of the delivery of science or knowledge, materials, and learning strategies themselves. The findings of this study show that a number of internal and external factors influence the growth of Islamic education learning, including education contributing to community intelligence, the influence of science and technology, environmental factors, boarding school institutions, learning strategies, and also professional educator factors can affect the development of education.